Towards an ontology for urban tourism - Gala A.P.-D.L. (2021)
Nowadays, diffusion and preservation of cultural heritage are being supported by technology on the Web. Thus, the online availability of urban tourism information, as part of cultural heritage, has been of enormous relevance to activate the tourism in many countries. The necessity of a well-defined and standard model for representing this knowledge is being managed by semantic web technologies, such as ontologies. However, current proposals represent partial knowledge of cultural heritage. In this context, this work proposes an ontology for indoor and outdoor environments of a city to represent the cultural heritage knowledge based on the UNESCO definitions. This ontology has a three-level architecture (Upper, Middle, and Lower ontologies) in accordance with a purpose of modularity and levels of specificity. To demonstrate the utility and suitability of our proposal, we have developed a parser to map and convert a museum repository (in CSV format) to RDF triples. With this case of study, we demonstrated that, by using our ontology, it is possible to represent the knowledge of urban tourism domains of a city. © 2021 Owner/Author.